Kepemimpinan Partisipatif Tokoh Agama dan Tokoh Masyarakat Dalam Mewujudkan Pembangunan Berkelanjutan Di Desa Alamendah - Zaharah; Fitri Sabillah; Tyara Puji Kusumastusi; Deni Setiawan (Universitas Islam Raden Rahmat Malang, 2025)
Participatory leadership is a strategic approach to development that actively involves the community at every stage, from planning to evaluation. In rural contexts, religious and community leaders play a central role in driving social and economic change based on local and spiritual values. This study aims to examine the role of participatory leadership through local leaders and the Al-Ittifaq Islamic Boarding School in supporting sustainable development in Alamendah Village, Rancabali Subdistrict, Bandung Regency. The method used is descriptive qualitative with data collection techniques through in-depth interviews, observation, and documentation, with community leaders as the primary informants. Data analysis used the Miles and Huberman model. The results of the study indicate that participatory leadership in Alamendah Village is capable of forming a cohesive social structure, strengthening the local agro-industry-based economy, and preserving culture and religious values. These findings confirm that local strength is the main foundation of sustainable village development and contributes to the development of a community-based development model that is contextual and aligned with spiritual values.